Effect of initial retinal thickness on outcome of intravitreal bevacizumab therapy for diabetic macular edema - Mushtaq B (Dove Medical Press, 2014)
Bushra Mushtaq,1,* Niall J Crosby,1,* Antonios T Dimopoulos,1 Peck Lin Lip,1 Panagiota Stavrou,1 Samer El-Sherbiny,1 Yit Yang2 1Birmingham and Midland Eye Centre, City and Sandwell National Health Service Trust, Birmingham, West Midlands, UK; 2Life and Health Sciences, Aston University, Birmingham, West Midlands, UK*These authors contributed equally to this workPurpose: To investigate whether eyes with diabetic macular edema (DME) and central retinal thickness (CRT) >400 µm had better visual and anatomical outcomes compared to eyes with a CRT <400 µm when treated with intravitreal bevacizumab in a real-world setting.Patients and methods: Patients undergoing intravitreal bevacizumab therapy for DME were identified from the departmental database of a tertiary referral unit. Following the initial injection, a retreatment was performed for any persistent macular edema, unless there had been no previous response to repeated doses. Recorded parameters included visual acuity, CRT on optical coherence tomography (spectral domain optical coherence tomography [SD-OCT]), and SD-OCT characteristics. Comparisons were made between data at baseline and 12 months after the first injection, and differences were tested for statistical significance using the Student's t-test.Results: In all, 175 eyes of 142 patients were analyzed. Patients in group 2 (CRT >400 µm) had significantly more injections than group 1 (CRT <400 µm) (4.0 versus 3.3; P=0.003). Both groups had similar numbers of eyes with preexisting epiretinal membrane and/or vitreomacular traction at baseline. The reduction in CRT was significantly greater in group 2 when compared to group 1 (P<0.0001). In terms of visual gain between baseline and month 12, each gained significantly by a mean of 0.12 logarithm of the minimum angle of resolution units (P=0.0001), but there was no difference between groups 1 and 2 (P=0.99).Conclusion: These results do not support a 400 µm baseline CRT cut-off for treating DME with bevacizumab, in contrast to published data on ranibizumab. Our results also indicate that patients with a thicker CRT require more bevacizumab injections, making treatment less cost-effective for these patients. Our results could be used by practitioners to support the use of bevacizumab in DME without applying a CRT cut-off.Keywords: anti-VEGF therapy, central retinal thickness, ranibizumab, intravitreal injection, optical coherence tomography